Socio-demographic potential of human resources in the Visegrad regions - Koišová, Eva; Masárová, Jana; Ivanová, Eva (Journal of Business Economics and Management, 2021)
Human resources are the key factor in the development of countries and regions. They affect the prosperity and competitiveness of the countries and regions. The purpose of the study was to assess the human resource potential in the V4 countries and to identify the groups of regions that share similar socio-demographic characteristics. Changes in these characteristics were tracked in the years of 2000, 2008, 2016 at the NUTS II level. Hierarchical cluster analysis was utilised as the main research method in order to identify the groups of regions where measures need to be taken to maintain regional development. We found out that the best conditions for the potential of human resources are concentrated mainly in metropolitan areas. On the other hand, there are regions that do not make sufficient use of their potential in the area of human resources development, e.g. the region of Východné Slovensko. It is the region with future prospects of human resource potential In the future it is necessary to remove shortcomings and low human resources potential in lowperforming regions.